Textbook of podiatric medicine - Hayes, Catherine (Lecturer in health) (M & K Publishing, 2017)
Globally, podiatric medicine has evolved significantly in both its depth and scope of practice. Continual innovation and a dynamic response to the call for evidence-based practice have led to a rapid revolution in podiatric education, research and practic.